The Stability Maintenance of Protein Drugs in Organic Coatings Based on Nanogels - Hongzhao Qi; Lijun Yang; Peipei Shan; Sujie Zhu; Han Ding; Sheng Xue; Yin Wang; Xubo Yuan; Peifeng Li (MDPI AG, 2020)
Protein drugs are often loaded on scaffolds with organic coatings to realize a spatiotemporal controlled release. The stability or activity of protein drugs, however, is largely affected by the organic coating, particularly with organic solvents, which can dramatically reduce their delivery efficiency and limit their application scope. In spite of this, little attention has been paid to maintaining the stability of protein drugs in organic coatings, to date. Here, we used catalase as a model protein drug to exploit a kind of chemically cross-linked nanogel that can efficiently encapsulate protein drugs. The polymeric shells of nanogels can maintain the surface hydration shell to endow them with a protein protection ability against organic solvents. Furthermore, the protection efficiency of nanogels is higher when the polymeric shell is more hydrophilic. In addition, nanogels can be dispersed in polylactic acid (PLA) solution and subsequently coated on scaffolds to load catalase with high activity. To the best of our knowledge, this is the first use of hydrophilic nanogels as a protection niche to load protein drugs on scaffolds through an organic coating, potentially inspiring researchers to exploit new methods for protein drug loading.